2010
DOI: 10.17221/10/2009-pps
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity and development rate of the bird cherry-oat aphid, Rhopalosiphum padi (L) (Hom.: Aphididae) on six wheat cultivars

Abstract: Taheri S., Razmjou J., Rastegari N. (2010): Fecundity and development rate of the bird cherry-oat aphid, Rhopalosiphum padi (L) (Hom.: Aphididae) on six wheat cultivars. Plant Protect Sci., 46: 72-78.Rhopalosiphum padi is a polyphagous species with a nearly worldwide distribution. Biological parameters of this aphid on six commonly grown wheat cultivars in the Fars province including Chamran, Darab2, Shiraz, Ghods, Marvdasht and Niknezhad were investigated at the two-leaf stage of wheat. The experiments were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 29 publications
6
4
0
Order By: Relevance
“…Previous and present results suggest that, the R o values vary according to the aphid species and biotypes, temperature degrees and / or cultivars & experimental methods. These differences in the net reproductive rate may have been caused by host plant effect as well as possibly aphid species and biotype (Tsai and Wanga, 2001;Özgökçe and Atlihan, 2005;Razmjou et al, 2006;Mirmohammadi et al, 2009;Taheri et al, 2010 andJahan et al, 2014). Our results show that R o and r m of the grapevine aphid on "Superior" grape variety ranged from 1.30 to 6.30 and 0.144 to 0.026, respectively, confirming the resistance of the noted variety to the aphid.…”
Section: Elsupporting
confidence: 69%
“…Previous and present results suggest that, the R o values vary according to the aphid species and biotypes, temperature degrees and / or cultivars & experimental methods. These differences in the net reproductive rate may have been caused by host plant effect as well as possibly aphid species and biotype (Tsai and Wanga, 2001;Özgökçe and Atlihan, 2005;Razmjou et al, 2006;Mirmohammadi et al, 2009;Taheri et al, 2010 andJahan et al, 2014). Our results show that R o and r m of the grapevine aphid on "Superior" grape variety ranged from 1.30 to 6.30 and 0.144 to 0.026, respectively, confirming the resistance of the noted variety to the aphid.…”
Section: Elsupporting
confidence: 69%
“…The most reduction in yield was caused by feeding by sucking the sap and depriving the plant of nutrients during the seedling stage. The loss of yield could be reach up to 60% if the mean density of aphids reached about 10-20 aphids per tiller (Taheri et al, 2010 andPapp andMesterhazy, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The development, survival and reproductive potential of R. padi were investigated by Abdel-Rahman et al (2002), they found that 24ºC was the optimum temperature. It completes its life cycle on various hosts particularly maize, barley, oats and wheat (Taheri et al, 2010).…”
Section: Introductionmentioning
confidence: 99%